PENGARUH DISIPLIN KERJA DAN PROFESIONALISME KARYAWAN TERHADAP KINERJA KARYAWAN DI BMT UGT SIDOGIRI CABANG BANYUWANGI SELATAN - Yuyun Purnama Sari; Eko Budiywono (Jurnal Ekonomi Syariah Darussalam, 2025)
This type of research is quantitative descriptive. The hypothesis proposed is that there is a positive and significant influence between Work Discipline (X1) and Employee Professionalism (X2) on Employee Performance (Y) both simultaneously and partially. This research was conducted on BMT UGT Sidogiri South Banyuwangi Branch employees, 30 respondents. The sampling technique used is proportionate stratified random sampling technique. The independent variables in this study are Work Discipline (X1) and Employee Professionalism (X2), while the dependent variable is Employee Performance (Y). The data analysis method in this study uses the technique of Multiple Linear Regression Analysis. The results of this study indicate that the variable work discipline has a positive and significant effect on employee performance. The professionalism variable has a positive and significant effect on employee performance. Variable work discipline and professionalism of employees together have a positive and significant effect on employee performance that is equal to 67.8% while the remaining 32.2% is influenced by other variables outside this study.